2015
DOI: 10.1038/srep17102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes Mellitus on Survival in Patients with Pancreatic Cancer: A Systematic Review and Meta-analysis

Abstract: Concurrent diabetes has been linked with an increased risk of death in many cancers, but findings in pancreatic cancer have been inconsistent. We performed a systematic review and meta-analysis to assess the effect of diabetes on survival in patients with pancreatic cancer. Of 4, 463 original articles, 41 were included in the review; 29 studies with 33 risk estimates were included in the meta-analysis. In the overall comparison of patients with pancreatic cancer and diabetes with their nondiabetic counterparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 65 publications
2
43
1
2
Order By: Relevance
“…Taken together our data suggest that pre-operative recent-onset DM, but not long-lasting DM or post-operative new-onset DM, has an impact on the prognosis of PDAC. Our results are in agreement with a recent meta-analysis reporting that preexisting DM in PDAC is associated with increased risk of mortality [57]. Of note, the meta-analysis showed that the risk of mortality was higher in patients with resected or resectable cancer than in those with nonresectable cancer and was higher in patients with recent-onset DM than in those with long-lasting DM [57].…”
Section: Discussionsupporting
confidence: 92%
“…Taken together our data suggest that pre-operative recent-onset DM, but not long-lasting DM or post-operative new-onset DM, has an impact on the prognosis of PDAC. Our results are in agreement with a recent meta-analysis reporting that preexisting DM in PDAC is associated with increased risk of mortality [57]. Of note, the meta-analysis showed that the risk of mortality was higher in patients with resected or resectable cancer than in those with nonresectable cancer and was higher in patients with recent-onset DM than in those with long-lasting DM [57].…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis revealed that with T2DM have about a 5 % higher risk of CRA than newly diagnosed diabetes patients, revealing the duration of T2DM as a risk factor for CRA. A possible explanation is that known T2DM patients’ bowels are exposed to hyperinsulinemia or a hyperglycemic environment for a longer time, and such hormonal or metabolic abnormalities (according to former study [ 60 ]) could affect tumour growth. However, some studies reported that metformin use was a protective factor of CRA [ 33 ] and cancer [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings emphasise the need to distinguish the significance of aetiological factors that are shared by both PC and DM. There is also a need to investigate the impact of [6,8].…”
Section: Discussionmentioning
confidence: 99%